Pengaruh Gender terhadap Prestasi Belajar Mahasiswa dengan Pendekatan SEM-PLS - Reny Amalia Permata; Syaidatussalihah Amalia Syaidatussalihah; Ade Kurniawan (Jurnal Pendidikan Matematika : Judika Education, 2022)
This study aims to determine the effect of gender on student achievement at the Medica Farma Husada Mataram Polytechnic in terms of activities, student learning styles and lecturer performance. In this study using SEM-PLS analysis with SmartPLS software. The sampling technique used is a simple random sample with a total sample of 92 students of the Polytechnic Medica Farma Husada Mataram with details of 49 male students and 43 female students. The results showed that the percentage of the influence of activity, learning style and lecturer performance on learning achievement for the female gender was 53% while the remaining 47% was influenced by other factors. As for the male gender, the magnitude of the influence of activity, learning style and lecturer performance on learning achievement is 55% while the remaining 45% is influenced by other factors. In conclusion, the influence of learning styles, both female and male gender, is significant on learning achievement. Keywords: SEM-PLS, Gender, learning achievement